Pengaruh Literasi dan Inklusi Keuangan Syariah Terhadap Manajemen Keuangan Syariah pada Generasi Z - Wangi, Bintang Adrian Sena; Susanto, Eko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The growth of the Islamic economy in Indonesia is currently so rapid, the benchmark is financial literacy and inclusion in accordance with the provisions and principles of sharia. It plays an important role in improving the quality of personal and public financial management, especially among Generation Z in the city of Depok. This research aims to determine the effect of Islamic financial literacy and inclusion on Islamic financial management in Generation Z in Depok city. This research method uses a quantitative approach with information collection methods obtained from 100 respondents through distributing questionnaires. The results of this study show that Islamic financial literacy does not have a positive effect on Islamic financial management variables with a significance value of 0, 331> 0, 05. Islamic financial inclusion has a positive influence on Islamic financial management with a significance value of 0, 049 < 0, 05. The simultaneous test results show that Islamic financial literacy and inclusion each have an influence on financial management in generation Z of Depok city, the significance value is 0, 000 < 0, 05. This study provides an understanding of Islamic financial literacy and inclusion in the application of Islamic financial management more wisely and ethically among the younger generation in order to achieve financial and spiritual well-being.